2012
DOI: 10.1177/0040517511402121
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of acoustical characteristics and sound absorption coefficient of woven fabrics

Abstract: The amount of research conducted on sound absorption properties of woven fabrics in comparison to nonwoven and spacer textile fabrics is very limited. The main aim of this research is to study acoustical and sound absorption properties of woven fabrics. Normal incident sound absorption coefficient was determined via the impedance tube method. To achieve the objective of the research, general acoustical properties of textiles together with existing standards were thoroughly studied. Samples of woven fabrics hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 5 publications
0
48
0
Order By: Relevance
“…Studies in fluid behavior in fibrous porous media are also greatly beneficial in thermal insulations, paper products, fibrous filters and membranes, polymeric industries and physiological systems and processes [60]. While in most of these applications, determination of the permeability traditionally is accomplished through experimental Figure 8.…”
Section: Comparison Of Results With Empirical and Analytical Availablmentioning
confidence: 99%
“…Studies in fluid behavior in fibrous porous media are also greatly beneficial in thermal insulations, paper products, fibrous filters and membranes, polymeric industries and physiological systems and processes [60]. While in most of these applications, determination of the permeability traditionally is accomplished through experimental Figure 8.…”
Section: Comparison Of Results With Empirical and Analytical Availablmentioning
confidence: 99%
“…Sound absorbency of a novel knitted spacer fabric, which can be used in automotive upholstery and has the potential for greater sound absorbency than a conventional plain knitted fabric and its derivatives 7 . Research work done using samples of woven fabrics having varying structural elements shows that the sound absorption coefficient of woven fabrics is influenced by both density and porosity of fabrics 8 .In present scenario noise pollution is a major problem faced globally. Noise pollution affects both health and behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The sound absorption coefficient of thin woven fabric is usually lower than that of bulk nonwoven fabric. It has been reported that plain fabric has better sound absorption properties than other texture types, and fabric made of rotor‐spun yarns could absorb acoustic energy more effectively than ring‐spun or compact yarns . In this work, plain cotton fabric made of rotor‐spun yarns was used, and the measured results are shown in Table and Fig.…”
Section: Resultsmentioning
confidence: 98%